Pengaruh Gaya Kepemimpinan, Jenjang Karir, Lingkungan Kerja Fisik Terhadap Kepuasan Kerja Perawat Melalui Efikasi Diri Sebagai Variabel Intervening Pada Rumah Sakit Jiwa Dan Ketergantungan Obat Engku Haji Daud - Diana, Kurnia; Ngaliman; Wayan Catrayasa, I (Bahtera Inovasi, 2024)
Nursing services are very important and goal-oriented services that focus on the implementation of nursing care. Improving the quality of nursing services is a challenge for nurses because nurses are professional staff who have the longest contact with patients, in contrast to medical services and other health services which only require a relatively short time to provide health services to their clients. This research is used for explanatory purposes ( explanatory or confirmatory), namely explaining the causal relationship between variables through hypothesis testing. This research is correlational in nature, namely research that attempts to see whether two or more variables are related and what direction the relationship takes. Based on the results of the research data analysis above, a conclusion can be made in this research as follows: Leadership Style has a significant influence on Self-Efficacy. Career level does not have a significant influence on Self-Efficacy. Work Environment has a significant influence on Self-Efficacy. Leadership Style has a significant influence on Job Satisfaction. Career Path has a significant influence on Job Satisfaction. Work Environment has a significant influence on Job Satisfaction. Self-Efficacy has a significant influence on Job Satisfaction. Leadership Style through Self-Efficacy does not have a significant influence on Job Satisfaction through the path coefficient results. Career Path through Self-Efficacy does not have a significant influence on Job Satisfaction through the path coefficient results. Work Environment through Self-Efficacy has a significant influence on Job Satisfaction through the results of the path coefficient.